Gordon Bennett's Home Decor : the joker in the pack - I. McLean (Law Text Culture, 1998)
The repeal of terra nullius in the Mabo case may have exposed the mythology which secured the British occupation and exploitation of Australia, but it did not foreclose the myth itself. The colonial ideologies that created a Manichean society based on racist lines are as strong as ever. This, anyway, is the disconcerting message of Gordon Bennett's art, and probably why viewers find his art 'in your face', as I recently overheard one teacher saying to students in the Museum of Contemporary Art in Sydney.